2022
DOI: 10.2147/jhc.s369951
|View full text |Cite
|
Sign up to set email alerts
|

Serum IGF-1 Scores and Clinical Outcomes in the Phase III IMbrave150 Study of Atezolizumab Plus Bevacizumab versus Sorafenib in Patients with Unresectable Hepatocellular Carcinoma

Abstract: Purpose Child-Turcotte-Pugh class A (CTP-A) in unresectable hepatocellular carcinoma (HCC) is the standard criterion for active therapy and clinical trial enrollment. We hypothesized that insulin-like growth factor-1 (IGF-1) derived scores may provide improved survival prediction over CTP classification. This study aimed to evaluate the potential prognostic and predictive effects of IGF-1 derived scores in the phase III IMbrave150 study. Patients and Methods Baseline an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“… 109 A biomarker study from the IMbrave150 pool showed that high baseline IGF-1 level is associated with improved OS in both the atezolizumab–bevacizumab and sorafenib arms, and it was suggested as a prognostic but not predictive biomarker. 96 Also, patients with decreased IGF-1 during treatment showed poor OS compared to stable IGF-1 in both the combination and sorafenib arms, which suggests IGF-1 as a surrogate marker for survival for both treatments. Notably, relatively few patients had decreased IGF-1 (32 cases in atezolizumab–bevacizumab and 14 cases in sorafenib) during treatment, so interpretation from the findings should be done with caution.…”
Section: Prognostic and Predictive Biomarkers For Advanced Hcc From M...mentioning
confidence: 96%
See 2 more Smart Citations
“… 109 A biomarker study from the IMbrave150 pool showed that high baseline IGF-1 level is associated with improved OS in both the atezolizumab–bevacizumab and sorafenib arms, and it was suggested as a prognostic but not predictive biomarker. 96 Also, patients with decreased IGF-1 during treatment showed poor OS compared to stable IGF-1 in both the combination and sorafenib arms, which suggests IGF-1 as a surrogate marker for survival for both treatments. Notably, relatively few patients had decreased IGF-1 (32 cases in atezolizumab–bevacizumab and 14 cases in sorafenib) during treatment, so interpretation from the findings should be done with caution.…”
Section: Prognostic and Predictive Biomarkers For Advanced Hcc From M...mentioning
confidence: 96%
“…Serum IGF-1 and AFP levels were suggested as surrogate and/or prognostic biomarkers by the exploratory studies from the IMbrave150 and GO30140 cohorts. 96 , 97 As the liver synthesizes the majority of IGF-1, IGF-1 has been proposed as a liver synthetic function marker. 109 A biomarker study from the IMbrave150 pool showed that high baseline IGF-1 level is associated with improved OS in both the atezolizumab–bevacizumab and sorafenib arms, and it was suggested as a prognostic but not predictive biomarker.…”
Section: Prognostic and Predictive Biomarkers For Advanced Hcc From M...mentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of antiangiogenic therapy and immunotherapy has demonstrated superior antitumour properties and significantly improved patient survival. In a phase III clinical trial of renal cell carcinoma, researchers found that the use of bevacizumab combined with the PD-1 inhibitor atezolizumab significantly improved the overall survival and progression-free survival rates of patients compared with sorafenib alone ( 174 ). Similarly, nivolumab (anti-PD-1 antibody) plus cabozantinib showed superior progression-free survival, overall survival, and objective response compared with sunitinib for the treatment of renal cell carcinoma ( 175 ).…”
Section: Anti-angiogenic Therapy Resistance and Combination Therapymentioning
confidence: 99%
“…Consequently, the novel combination of IGF-1 levels and Child-Pugh scores may help improve patient stratification in clinical practice. 68 …”
Section: Biomarkersmentioning
confidence: 99%